Kulturowe znaczenie biżuterii hellenistycznej ozdobionej węzłem Heraklesa = The cultural importance of Hellenistic jewelry decorated with a knot of Herakles - Bednarczuk, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discussed the cultural importance of Hellenistic jewelry decorated with node, which was known as the knot of Heracles. The article speaks to the concept by Michael Pfrommera, meaning that a node of Heracles in the Hellenistic period was associated with the sphere of the Macedonian politics. Critique has been subjected to the concept by Hedwig Kenner, which sources popularity node in Greek art saw in specifically understood the religious sphere and the ?inner nature of deity?.
Keywords: Heraklesa węzeł; biżuteria hellenistyczna; amulet; symbol; misteria; Heracles knot; Hellenistic jewelry; mysteries